Incorporating Memes and Instagram to Enhance Students Participation - Purnama, Agnes Dian (LLT Journal: A Journal on Language and Language Teaching, 2017)
Todays teaching and learning faces more challenges as technology keeps on updating itself. Teachers are expected to adopt as many as possible technology products to promote students engagement in classroom activity. Utilizing technology products may help teachers to decrease students boredom inside classroom since it proposes a new kind of activity. The main purpose is to create an enjoyable teaching and learning environment as well as to trigger students to be creative. By highlighting youths characteristics that tend to be visual and addicted to rapid information, memes and Instagram may be used as one of the strategies to develop an innovative teaching and learning process.